Spacer improvement for efficient and fully printable mesoscopic perovskite solar cells. Issue 17 (6th February 2017) - Liu, Tongfa; Rong, Yaoguang; Xiong, Yuli; Mei, Anyi; Hu, Yue; Sheng, Yusong; Jiang, Pei; Hou, Xiaomeng; Duan, Miao; Guan, Yanjun; Hong, Li; Han, Hongwei
Abstract : Highly dispersible TiO2 @ZrO2 nanoparticles are synthesized to prepare an ultra-flat and crack-free spacer film, leading to an enhanced insulating ability compared to a conventional spacer. Abstract : Highly dispersible TiO2 @ZrO2 nanoparticles are synthesized to prepare an ultra-flat and crack-free spacer film, leading to an enhanced insulating ability compared to a conventional spacer. The average power conversion efficiency of fully printable mesoscopic perovskite solar cells is improved from 10.2% to 12.5%, and the highest steady output power conversion efficiency is 13.8%.